1997
DOI: 10.1111/j.1600-0560.1997.tb01322.x
|View full text |Cite
|
Sign up to set email alerts
|

Fibrohistiocytic differentiation in subcutaneous fatty tumors

Abstract: Subsets of dendritic cells, fibroblasts which express the human progenitor cell antigen CD34 or histiocytes which express coagulation factor XIIIa (FXIIIa), are present in fat and in collagenous connective tissue. As components of the microvascular unit, these fibrohistiocytic cell subsets may interact during stromal remodeling, repair, and neoplasia. We studied white fat and subcutaneous fatty tumors to determine if CD34 and/or FXIIIa+ "fibrohistiocytic" dendritic cell subsets are involved in their morphogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(5 citation statements)
references
References 41 publications
(66 reference statements)
0
5
0
Order By: Relevance
“…The presence of CD34 + cells in lipomas is well-known 8 and is used to confirm the histological diagnosis 9 , 10 . A varying amount of CD34 + spindle cells is generally detectable within the lesion 11 , 12 : they are more numerous near vessels 13 , whereas the adipocytes and the other differentiated cells are negative for CD34 expression 14 , leading to the hypothesis of an abnormal proliferation of normal CD34 perivascular cells in various types of lipomas and some liposarcomas 13 . A proliferation of CD34 + dendritic cells in a variety of fibrovascular and fibrohistiocytic tumours has been reported 15 and hypothesized for Kaposi's sarcoma, also too 16 .…”
Section: Introductionmentioning
confidence: 99%
“…The presence of CD34 + cells in lipomas is well-known 8 and is used to confirm the histological diagnosis 9 , 10 . A varying amount of CD34 + spindle cells is generally detectable within the lesion 11 , 12 : they are more numerous near vessels 13 , whereas the adipocytes and the other differentiated cells are negative for CD34 expression 14 , leading to the hypothesis of an abnormal proliferation of normal CD34 perivascular cells in various types of lipomas and some liposarcomas 13 . A proliferation of CD34 + dendritic cells in a variety of fibrovascular and fibrohistiocytic tumours has been reported 15 and hypothesized for Kaposi's sarcoma, also too 16 .…”
Section: Introductionmentioning
confidence: 99%
“…In embryonic specimens, by 6 weeks, there is a band of CD34+ dendritic cells at the junction of the deep reticular dermal and subcutaneus anlagen. This distribution suggests that the CD34+ deep dermal dendrocytes might contribute to the formation of the primitive fat organ 11 . These studies might be a useful clue to understanding why the spindle cells of SCL give a strong reaction with CD34.…”
Section: Discussionmentioning
confidence: 74%
“…The SCL are thought to arise from a fibroblast‐like primitive adipocyte precursor cell shown in electron microscopy studies of fat and conventional lipoma as pericytic cells present along the interstitial capillaries 11 . In embryonic specimens, by 6 weeks, there is a band of CD34+ dendritic cells at the junction of the deep reticular dermal and subcutaneus anlagen.…”
Section: Discussionmentioning
confidence: 99%
“… 7 Another interesting theory is the fibrohistiocytic differentiation of cells in fatty tumors: CD34 + perimysial fibroblasts and interstitial dendritic cells appear to undergo an adipocytic transformation, contributing to the pathogenesis of intramuscular lipomas. 8 Moreover, an immunohistochemical study demonstrated that structures within the head and neck region are abundantly covered with CD34 + fibrous tissues, especially the parotid gland and the sternocleidomastoid muscle. 9 This can potentially explain how an intramuscular lipoma could have arisen within the SCM muscle.…”
Section: Discussionmentioning
confidence: 99%